Micropropagation and Cellular Behaviour Changes During in vitro Flowering of Impatiens balsamina - Mohamed, Normadiha; Taha, Rosna Mat; Razak, Ummi Nur Ain Abdul (Sociedade Brasileira da Ciencia das Plantas Daninha, 2019)
In this study, the micropropagation of Impatiens balsamina was established from stem and shoot explants. The effects of GA3 and glutathione on the morphogenesis of this species were also investigated, in order to induce in vitro flowering. It was found that the optimum in vitro plant regeneration was achieved on MS medium supplemented with 1.0 mg L-1 GA3 and in vitro flowering was also obtained from the same medium after 4 weeks of culture. To understand cellular behavior during in vitro flowering, Mitotic Index (MI), chromosome counts, measurement of mean cell and nuclear areas, DNA measurements and ploidy levels were analyzed from in vivo plants, in vitro grown plants and plantlets that flowered in vitro. The chromosome count was the same for all, 2x=2n=14 or n=7. However, it was observed that in vitro flowering plants of Impatiens balsamina had the highest percentage of polyploid cells (30.7%), based on a histogram plotted by the AxioVision 4.7 software. It was found that plant growth regulators, especially GA3, increased the polyploidy level of the meristematic root cells. © 2019, Sociedade Brasileira da Ciencia das Plantas Daninha. All rights reserved.